MCL1 is required for maintenance of intestinal homeostasis and prevention of carcinogenesis in mice - Healy, Marc Eamonn; Scherr, Anna-Lena; Schulze-Bergkamen, Henning; Heikenwälder, Mathias (Gastroenterology, 2020)
Background & Aims - Intestinal epithelial homeostasis depends on a tightly regulated balance between intestinal epithelial cell (IEC) death and proliferation. While the disruption of several IEC death regulating factors result in intestinal inflammation, the loss of the anti-apoptotic BCL2 family members BCL2 and BCL2L1 has no effect on intestinal homeostasis in mice. We investigated the functions of the antiapoptotic protein MCL1, another member of the BCL2 family, in intestinal homeostasis in mice. - Methods - We generated mice with IEC-specific disruption of Mcl1 (Mcl1ΔIEC mice) or tamoxifen-inducible IEC-specific disruption of Mcl1 (i-Mcl1ΔIEC mice); these mice and mice with full-length Mcl1 (controls) were raised under normal or germ-free conditions. Mice were analyzed by endoscopy and for intestinal epithelial barrier permeability. Intestinal tissues were analyzed by histology, in situ hybridization, proliferation assays, and immunoblots. Levels of calprotectin, a marker of intestinal inflammation, were measured in intestinal tissues and feces. - Results - Mcl1ΔIEC mice spontaneously developed apoptotic enterocolopathy, characterized by increased IEC apoptosis, hyperproliferative crypts, epithelial barrier dysfunction, and chronic inflammation. Loss of MCL1 retained intestinal crypts in a hyperproliferated state and prevented the differentiation of intestinal stem cells. Proliferation of intestinal stem cells in MCL1-deficient mice required WNT signaling and was associated with DNA damage accumulation. By 1 year of age, Mcl1ΔIEC mice developed intestinal tumors with morphologic and genetic features of human adenomas and carcinomas. Germ-free housing of Mcl1ΔIEC mice reduced markers of microbiota-induced intestinal inflammation but not tumor development. - Conclusion - The antiapoptotic protein MCL1, a member of the BCL2 family, is required for maintenance of intestinal homeostasis and prevention of carcinogenesis in mice. Loss of MCL1 results in development of intestinal carcinomas, even under germ-free conditions, and therefore does not involve microbe-induced chronic inflammation. Mcl1ΔIEC mice might be used to study apoptotic enterocolopathy and inflammatory bowel diseases.
Gesehen am 07.09.2020